2008
DOI: 10.1111/j.1365-2982.2008.01166.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to flagellin indicate reactivity to bacterial antigens in IBS patients

Abstract: One of the several possible causes of irritable bowel syndrome (IBS) is thought to be low-grade mucosal inflammation. Flagellin, the primary structural component of bacterial flagellae, was shown in inflammatory bowel disease patients to activate the innate and adaptive immunity. It has not yet been conclusively established if IBS patients show reactivity to luminal antigens. In 266 patients [112 IBS, 61 Crohn's disease (CD), 50 ulcerative colitis (UC) and 43 healthy controls (HC)], we measured antibodies to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(68 citation statements)
references
References 46 publications
4
64
0
Order By: Relevance
“…[49][50][51][52] However, most studies found no difference in the faecal levels of calprotectin and lactoferrin between IBS patients and healthy controls. 43,44,49,50,[52][53][54][55][56][57][58][59] Only one publication reported that increased levels of faecal calprotectin were correlated with pain severity; however, this result was observed in children displaying both functional abdominal pain and IBS. 60 Key point: (i) Typically, no changes in the levels of the faecal inflammatory markers calprotectin and lactoferrin are reported in IBS patients.…”
Section: Key Pointsmentioning
confidence: 69%
See 1 more Smart Citation
“…[49][50][51][52] However, most studies found no difference in the faecal levels of calprotectin and lactoferrin between IBS patients and healthy controls. 43,44,49,50,[52][53][54][55][56][57][58][59] Only one publication reported that increased levels of faecal calprotectin were correlated with pain severity; however, this result was observed in children displaying both functional abdominal pain and IBS. 60 Key point: (i) Typically, no changes in the levels of the faecal inflammatory markers calprotectin and lactoferrin are reported in IBS patients.…”
Section: Key Pointsmentioning
confidence: 69%
“…42 The potential activation of the innate gut immune system in IBS could be a sign of previous infection and/or ongoing low-grade inflammation. In this regard, increased faecal levels of the human beta-defensin HBD2, 43 an antimicrobial peptide produced by intestinal epithelial cells, and elevated blood concentrations of the A4-Fla2 and Fla-X bacteria-specific antibodies 44 38,46 Similarly, the Studies identified in PubMed literature search with the following key words:…”
Section: Resultsmentioning
confidence: 99%
“…Rectal infusion of fecal supernatants from IBS patients sensitizes mice to colorectal distension, which is suggested to occur via microbesecreted serine proteases, which activate protease-activated receptor-2 on nerve endings ( 16 -18 ). Th e direct eff ects on sensory nerves may also be compounded by activation of the innate and adaptive immune responses, as suggested by the elevated levels of antibodies against bacterial fl agella in IBS patients ( 19,20 ). Oral probiotic preparations aimed at restoring the " healthy commensal biota balance " have been met with much enthusiasm by IBS patients, and studies have shown Lactobacilli and Bifi dobacteria preparations both modulate immune function and improve IBS symptoms ( 21 -23 ).…”
Section: Role Of Microbiota In Ibsmentioning
confidence: 99%
“…As previously stated, current knowledge about the interaction between extracellular proteins and the GALT mainly derives from data involving commensal bacterial groups. In this context, it has been observed that some proteins secreted by the commensal microbiota might be responsible for the anomalous immune response observed in the framework of inflammatory bowel disease (Adams et al, 2008;Ivison & Steiner, 2008;Schoepfer et al, 2008).…”
Section: Proteins Secreted By Probiotic Bacteriamentioning
confidence: 99%